Return to Play Rates and Clinical Outcomes of Baseball Players Following Concomitant Ulnar Collateral Ligament Reconstruction and Indicated Ulnar Nerve Transposition (130). Issue 10 (31st October 2021) - Rao, Somnath; Willier, Donald; Gawel, Richard; Jack, Robert; D'Amore, Taylor; Cohen, Steven; Ciccotti, Michael
Objectives: Injury to the ulnar collateral ligament (UCL)—leading to medial elbow instability and concomitant ulnar neuropathy symptoms—is common in the overhead throwing athlete secondary to the repetitive stress that these individuals place on the elbow during the throwing motion. Treatment customarily involves UCL reconstruction (UCLR) and for those with preoperative ulnar neuropathy symptoms, concomitant ulnar nerve transposition (UNT) may also be warranted. The purpose of this study was to evaluate the return to play rates, clinical outcomes and more specifically rates of persistent ulnar nerve symptoms after concomitant UCLR and UNT in a cohort of baseball players with confirmed preoperative ulnar neuropathy symptoms. Methods: Patients who underwent concomitant UCLR and UNT from January 2008 to June 2018 were identified at one institution with a minimum of 2 years of follow-up. Additional inclusion criteria included athletes who identified as baseball players with a confirmed history of ulnar neuropathy symptoms. Exclusion criteria included patients who had any other concomitant open procedures at the time of surgery. After identifying the cohort, patients were contacted via phone to complete a Kerlan-Jobe Orthopedic Clinic Shoulder and Elbow Score (KJOC), Andrews-Timmerman (AT) Elbow Score, Mayo Elbow Performance Score (MEPS), Single Assessment Numeric Evaluation (SANE) score and a custom return to play questionnaire. Evidence for preoperative and postoperative ulnar nerve symptoms was elicited within the custom survey and corroborated with the provider's clinical notes. Sensory ulnar nerve symptoms were defined as having numbness and/or tingling sensations in the 5 th and ulnar half of the 4 th fingers. Motor ulnar nerve symptoms were defined as either exhibiting 1 st dorsal interosseous muscle weakness by inability to maintain finger abduction resistance, ulnar-sided hand grip weakness of inability to control precise movement of the 5 th digit. Results: During this time period, a total of 22 male baseball players underwent concomitant UCLR and UNT at a mean age of 18.9+/-2.1 years (range, 16-25). The mean follow-up was 6.1+/-2.4 years (range, 2.5-11.7 years). The cohort consisted of 15 pitchers and 7 position players. In total, 7 players competed in high school and 15 competed in college. Preoperatively, all 22 patients reported ulnar nerve sensory symptoms while only 4 (18.2%) patients reported ulnar nerve motor symptoms. Overall, 16 (72.3%) players were able to return to competitive play at an average of 11.2 months. Of the 6 that failed to return to play after surgery, 3 reported that persistent elbow symptoms were the reason for not returning to play while the other 3 reported losing the desire to return to play. At final follow-up, 7 (31.8%) patients reported of persistent sensory ulnar nerve sensory symptoms while 1 (4.5%) of these patients additionally reported persistent ulnar nerve motor symptoms. The mean postoperative patient reported outcome scores were as follows: KJOC: 77.9+/-20.9 (range, 14-100); MEPS: 92.7+/-12.7 (range, 45-100); AT Elbow Score: 86.1+/-17.1 (range, 30-100); SANE score: 85.5+/-14.8 (range, 50-100). Conclusions: While patient-reported outcome scores and return to play rates are reasonably high, this study demonstrates that following concomitant UCL reconstruction and ulnar nerve transposition for UCL insufficiency and associated ulnar neuropathy, rates of persistent ulnar neuropathy symptoms are persistently present in over 30% of patients. Currently, handling of the ulnar nerve in the setting of UCL insufficiency is debated and thus further investigation is warranted to optimize outcomes for this group of patients.